Microcavity Laser Based on Cholesteric Liquid Crystal Doped With Reactive Mesogen - Y. Li; D. Luo; R. Chen (IEEE Photonics Journal)
We demonstrate an omnidirectional laser from a 3-D Bragg microcavity, which is fabricated from a cholesteric liquid crystal that is doped with reactive mesogen. The wavelength of the laser is found to be determined by the position of the photonic bandgap that was formed within the 3-D Bragg microcavity. Compared with the laser from pure cholesteric liquid crystal microcavity, a rigid polymer network is formed within the microcavity due to the doped reactive mesogen. The polymer network successfully enhances the resistance ability of the 3-D Bragg microcavity to higher pump power by 1.5 times, thus leading to a more stable laser based on it. This laser may have potential use in optics, displays, and other photonic devices.